Preliminary approach to elucidate the role of pigment as a binding site for drugs and chemicals in anagen hairs: pigments as carriers for 3H-haloperidol in HaCaT/Sk-Mel-1 co-cultures - Pötsch-Schneider, Lucia Edeltraud; Emmerich, Patricia; Skopp, Gisela (International journal of legal medicine, 2002)
In view of the melanin-binding characteristics of haloperidol and its differential uptake by pigment- and non-pigment-producing cells, a co-culture of HaCaT with Sk-Mel-1 cell lines was performed to investigate whether melanosomes act as carriers for drug molecules associated with the pigments. Initially, HaCaT and Sk-Mel-1 cells were separately cultivated in the presence of 3H-haloperidol (400 pmol/ml medium ) for 28 days followed by subsequent co-cultivation in the absence of 3H-haloperidol for 5 days. The transfer of pigments into the keratinocytes during co-culture was confirmed by transmission electron microscopy. After the co-culture experiments a striking increase (≥ 50%) of 3H-haloperidol was observed in the pigmented HaCaT cells compared to the unpigmented keratinocytes. The present study proved the role of pigments as carriers for melanin-associated drug molecules. The results supported the hypothesis that hair pigment might be a factor affecting the outcome of hair assays for particular categories of commonly used licit and illicit substances. The chosen cell lines and the developed co-culture system may represent suitable in vitro models to study differential drug uptake into cell populations present in the skin or in the growing hair follicle as well as to elucidate drug uptake due to melanocyte-keratinocyte interactions.
Im Titel erscheint die Ziffer 3 hochgestellt
Gesehen am 27.04.2021